Photocatalytic degradation of tetracycline by TiO2/PVDF film photocatalyst: degradation mechanism and intermediates analysis - Mohmad Ameran, Hazlini; Abdullah, Abdul Halim; Tan, Yen Ping; Muhamad, Ernee Noryana; Ohno, Teruhisa; Ando, Yoshito (Springer, 2025)
One of the most commonly used antibiotics for humans and animals is tetracycline (TC). TC can indirectly cause harmful impacts on the environment by enhancing the risk of antibiotic-resistant pathogens. Removing TC from water is challenging but crucial for human health. This work prepared TiO2/PVDF film photocatalysts using the phase inversion method and evaluated their performance in degrading TC under UV light irradiation. The surface roughness and hydrophilicity of the TiO2/PVDF film photocatalysts improved with increasing addition of TiO2 to the photocatalyst films. The progress of TC degradation was monitored by UV–Vis spectroscopy, Liquid chromatography–mass spectroscopy (LC–MS), and chemical oxygen demand analysis. The PTi-6 film photocatalyst, comprised of 6 wt% TiO2 and 12.5% PVDF, exhibited the highest TC degradation efficiencies. pH 5 is the optimum pH for tetracycline degradation using TiO2/PVDF film. Based on the LC–MS results, the identified intermediates were used to propose the route of TC degradation. The PTi-6 film photocatalyst retained its photocatalytic efficiency for up to eight degradation cycles, proving the vast potential of the film to be applied in real-life situations.